Immunological relationship between Helicobacter pylori and anti-tumor necrosis factor α agents in inflammatory bowel disease - Han Huang; Chenxiao Gan; Yan Cai; Lingkang Wu (Central European Journal of Immunology)
Inflammatory bowel disease (IBD) is a group of diseases characterized by refractory and chronic inflammation of the bowel, which can be treated with biologics in clinical practice. Anti-tumor necrosis factor α (TNF-α) agents, which are among the most widely used biologics, alleviate the inflammatory activity in a variety of ways. Helicobacter pylori is a Gram-negative bacterium that colonizes the gastric mucosa, which could cause chronic inflammation and even induce gastric cancer. However, it has been suggested that H. pylori has a potential protective role in IBD patients. Yet there has been limited research on the mechanisms of the effect of H. pylori infection in IBD patients, and whether there is an interaction between H. pylori and anti-TNF-α agents. This review aims to summarize the possible mechanisms of H. pylori and anti-TNF-α agents in the development and treatment of IBD, and to explore the possible interaction between H. pylori infection and anti-TNF-α agents.